Protagonist Agency in Epistolary Fiction: Lady Susan by Jane Austen - Syarifah; Rahmah Fithriani; Pardi (Wanastra: Jurnal Bahasa dan Sastra, 2026)
Agency in literary studies is commonly approached as a moral or psychological quality of a character. However, such perspectives often overlook how agency is shaped by narrative form. This study addresses this gap by examining how the protagonist’s agency in Lady Susan is narratively constructed through epistolary mediation. This study examines the construction of the protagonist’s agency in Lady Susan, an epistolary novella in which action and intention are mediated through letters. Rather than treating agency as an ethical attribute, the study approaches agency as a product of textual mediation. Using a qualitative literary approach, the analysis employs close reading of selected letters to examine decision-making, narrative voice, and narrative consequences. This focus is significant because it clarifies how agency in epistolary fiction operates as a strategic and negotiated textual process rather than merely a reflection of character autonomy. The findings demonstrate that the protagonist’s agency is not represented as moral autonomy but as a strategic capacity negotiated through voice and social relations. Within the epistolary structure, agency emerges as a dynamic and textually constructed process.